Psychometric properties of the wellbeing literacy 6-item scale in Chinese military academy cadets - Jia, Zhen; Zheng, Fangfang; Wang, Feifei; Yang, Guoyu (Frontiers in Psychology, 2024)
Background Positive psychology is a vibrant field of study, and conceptualizations of the components of well-being have received a great deal of attention from researchers. The study of well-being literacy thus provides an innovative perspective for enhancing and sustaining individuals’ experiences of well-being. Objective This study aimed to examine the psychometric properties of the wellbeing literacy 6-item (Well-Lit 6) scale in Chinese military academy cadets. Methods A total of 3,218 undergraduate students from five military academies in China were recruited to complete questionnaires online. Results (1) The items of the scale showed high discrimination; (2) The alpha coefficient of the scale was 0.986 and the split-half reliability was 0.981, indicating high homogeneous reliability and split-half reliability; (3) The scale model fitted well and displayed structural validity; (4) The correlation between well-being literacy and related indicators was significant, and the calibration correlation and convergent-discriminant validity of the scale were high; (5) After gradually adding demographic variables, known predictors factors and well-being literacy, the ∆R2 for subjective well-being, life satisfaction, depression, and anxiety ranged from 0.036 to 0.067, 0.184 to 0.340, and 0.009 to 0.017, respectively, showing high incremental validity; (6) the total well-being literacy scores differed significantly by gender, grade, and parenting style. Conclusion The Chinese version of the Well-Lit 6 is reliable and valid in predicting and accessing the subjective well-being, life satisfaction, emotion regulation, and psychological resilience of Chinese military academy cadets.